PHONETIC TRANSCRIPTION IN SATISFACTORS: A PSYCHOLINGUISTIC STUDY - Ramadhan, Syahrul; Setiawan, Hendra (EDU-KATA, 2024)
Language is the only communication tool used by humans. The acquisition of language is the greatest form of human achievement. Acquisition occurs during childhood involving brain performance. Therefore, the use of language is an important aspect for humans to carry out communication and social interaction. However, when using it, many language disorders are found, one of which is a lisp. This research will focus on discussing the language disorders of slurred people in adults aged 22 years, seen from the phonological aspect which includes phonetics and phonemics and studied through psycholinguistics. This research uses a qualitative approach using observation techniques. Data is processed using descriptive methods. The findings in the research were that subjects could pronounce the /r/ phoneme at the beginning and end of words, but subjects tended to replace the /r/ phoneme in the middle of words with the /l/ phoneme. Through a phonological lens, it was found that there were many aspirations when the subject encountered the /r/ phoneme, apart from that, the /r/ phoneme sounded mixed with the /e/ phoneme. Psycholinguistic studies found that the subject had never had an accident that resulted in serious injury to the brain's nerves. Factors that influence language fluency are physiological factors.